Analysis of Drinking Water Quality Directly Related to Health at Refill Depots in the South Bekasi Area, Indonesia - Rahmawati, Fri; Lumbantobing, Romauli (Eximia, 2023)
Water is a source of life for living things for daily needs. The dense population and limited water sources result in an increase in drinking water that is suitable for consumption. It has encouraged many people to look for alternative sources of drinking water, one of which consumes drinking water from refill depots. The research aims to analyze microbiological and inorganic chemical parameters in several drinking water sources from water depots in the South Bekasi area, Indonesia. Microbiological analysis of drinking water was carried out by identifying types of germs and inorganic chemical analysis using a spectrophotometer. Based on the study's results, three samples of drinking water were detected containing E.coli bacteria, and five samples of drinking water containing Pseudomonas sp. Inorganic chemical analysis shows that all samples contain inorganic chemical compounds (Ar, F, Cr, Cd, NO2, NO3, CN, Se) with concentrations below the maximum levels allowed by Minister of Health Regulation Indonesia.